Uji Aktivitas Antioksidan Ekstrak Etanol Buah Kelor (Moringa Oleifera Lamk) Asal Kecamatan Suppa Kabupaten Pinrang Dengan Metode DPPH: Ethanol Extract Antioxidant Activity Test Moringa Fruit (Moringa Oleifera Lamk) From Suppa District, Pinrang Regency Using the DPPH Method - Fahmi, Muhammad (Jurnal Novem Medika Farmasi, 2023)
Antioxidants are chemical compounds that can provide one or more electrons to free radicals, so that these free radicals can be reduced. This research aims to determine the antioxidant activity of ethanol extract of Moringa fruit (Moringa oelifera Lamk.) from Suppa District, Pinrang Regency using the DPPH method. Moringa fruit simplicia is extracted using 70% ethanol by maceration. Testing for antioxidant activity against free radicals was analyzed using a visible spectrophotometer at a wavelength of 515 nm. The results of the analysis show that the antioxidant activity of the ethanol extract of Moringa fruit (Moringa oleifera Lamk.) from Pinrang Regency, Suppa District has an IC50 value of 1183.0914 μg/mL.